تجليات الاغتراب والحنين في شعر المدينة - بلعبدو, كوثر (كلية الأدب العربي والفنون, 2025)
تناول البحث دراسة وتحليل مظاهر الاغتراب والحنين في شعر المدينة عند "مبارك جلواح"، حيث يعكس الشاعر معاناة الذات في فضاء المدينة؛ يبرز من خلال التحليل محوران رئيسيان هما الاغتراب النفسي والاجتماعي، والحنين إلى الأصول والمكان الأول، حيث تتقاطع هذه المشاعر مع معاناة الشاعر من التحولات التي شهدتـها المدينة. تنطلق الدراسة للكشف عن العلاقة بين الشاعر والمدينة كرمز للتحولات الاجتماعية والثقافية،. كما يظهر الحنين في شعره من خلال استحضار الذكريات والأحبة، والأماكن التي شكلت جزءًا من هويته، في هذا السياق، يبرز التوتر بين باريس والجزائر، حيث لا يجد الشاعر مكانًا له في باريس، بينما تظل الجزائر مهما كانت الظروف، وطنه الأم. This study focuses on the exploration and analysis of the manifestations of alienation and nostalgia in urban poetry by Mabrouk Djelouah. The poet reflects the suffering of the self in the city space; two main axes emerge from the analysis: psychological and social alienation, and longing for origins and the first place. These feelings intersect with the poet's anguish in response to the transformations the city has undergone. The study seeks to uncover the relationship between the poet and the city as a symbol of social and cultural changes. Nostalgia appears in his poetry through the evocation of memories, loved ones, and places that shaped his identity. In this context, the tension between Paris and Algeria is highlighted: the poet finds no place for himself in Paris, while Algeria remains, despite everything, his homeland
نماذج من شعر مبارك جلواح
Keywords: الاغتراب، الحنين، المدينة، مبارك جلواح، الجزائر، باريس; alienation, nostalgia, city, Mabrouk Djelouah, Algeria, Paris